THE IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT IN IMPROVING THE QUALITY OF JUNIOR HIGH SCHOOL EDUCATIONAL ADMINISTRATION - EMMA SITI MARYAMAH (CV KULTURA DIGITAL MEDIA, 2025)
Saddened by this background, in the practical setting in junior high schools, there are still education providers who think that administration is not important. In reality, junior high schools in their implementation require Education Administration including collecting, recording, managing, sending, and storing. This Education management requires good human resources for managing education in an order of School Based Management (MBS). Based on research findings, the implementation of the MBS pillar implementation program in SMP Manggala runs according to management functions through planning, organizing, monitoring, coordinating to evaluating in achieving the purposes of a program of an educational institution